Alexa, Reshape My Supply Chain: How Voice Commerce Alters Demand Forecasting, Fulfillment Speed, and Marketing Messaging: JEL Classification: D91; L81; M15; M31; O33 - Simon Dzreke; Semefa Elikplim Dzreke (Maroon Journal De Management, 2026)
The simple utterance "Alexa, order more batteries!" triggers significant operational discontinuities across global supply chains. Voice commerce, now constituting 35% of smart speaker interactions, fundamentally restructures retail logistics, consumer expectations, and marketing psychology. With 47% of voice orders demanding last-minute, low-margin essentials like toilet paper or allergy medicine, traditional demand forecasting succumbs to pronounced "voice shock," characterized by 27% higher volatility spikes concentrated within narrow 15-minute windows. Analysis of 2.3 million anonymized voice transactions, combined with eye-tracking studies of 450 participants and logistics simulations, reveals a critical shift: consumers now expect 2-hour delivery for voice-activated purchases, representing a 96% compression from the established 2-day standard for mobile or web orders. This heightened urgency necessitates hyperlocal fulfillment pods within five miles of users, demonstrably outperforming regional warehouses by reducing delivery failures by 44%. Critically, sonic marketing adheres to a strict "3-second rule," where audio advertisements exceeding this duration experience 62% abandonment. This research introduces a voice-optimized framework demonstrating how enterprises can leverage micro-fulfillment algorithms, ethical conversational design, and predictive audio mnemonics to convert voice-induced operational chaos into sustainable competitive advantage. The era of voice-driven supply chains represents a contemporary imperative.